2020
DOI: 10.3390/e22070771
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-Time Fractional, Variable-Order PID Controller for a Plant with Delay

Abstract: In this paper, we discuss the implementation and tuning algorithms of a variable-, fractional-order Proportional–Integral–Derivative (PID) controller based on Grünwald–Letnikov difference definition. All simulations are executed for the third-order plant with a delay. The results of a unit step response for all described implementations are presented in a graphical and tabular form. As the qualitative criteria, we use three different error values, which are the following: a summation of squared error (SSE), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, the application of fractional-variable or-der is not unique and exists various solutions to this problem [24], [25]. Therefore, various variable-order FOPID controller implementations can be found in the literature [26]- [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the application of fractional-variable or-der is not unique and exists various solutions to this problem [24], [25]. Therefore, various variable-order FOPID controller implementations can be found in the literature [26]- [29].…”
Section: Introductionmentioning
confidence: 99%
“…It results that for t → ∞, implementations of fractional-order integrator have no longer the integration property. In [6], [44] it is shown that using various optimization techniques reduces the steady-state error. Another way to eliminate steady-state error is proposed in [45], [46], where integer-order integration combined with fractional-order derivative is used to model the fractional-order integrator.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike integer-order operators, the intrinsic multiscale nature of fractional operators enabled a very unique and effective approach to model historically challenging physical processes involving, as an example, nonlocality or memory effects. Indeed, many of the early applications of FC to physical modeling included viscoelastic effects [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], nonlocal behavior [ 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], anomalous and hybrid transport [ 9 , 10 , 11 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], fractal media [ 12 , 31 , 32 , 33 , 34 , 35 ], and even control theory [ 36 , 37 , 38 , 39 ]. The interested reader is referred to the work in [ 40 ] for a detailed account of the birth and evolution of fractional calculus.…”
Section: Introductionmentioning
confidence: 99%
“…In the paper a novelty variable, the fractional-order PID (VFOPID) [6,28,[33][34][35][36][37][38][39][40][41] controller synthesis is proposed. It consists of dividing the closed-loop system discrete-transient time division into the finite time intervals over which are defined fractional orders summation and differentiation functions.…”
Section: Introductionmentioning
confidence: 99%